Fast Phased Array Calibration by Power-Only Measurements Twice for Each Antenna Element - Guolong He; Xin Gao; Hui Zhou (International Journal of Antennas and Propagation)
This paper proposes a novel power-only measurement method for phased array antenna calibration. Besides the total array power, only one phase shift and two power measurements for each array element are required to determine the element complex electric field distortion, one by shifting the element’s phase of π/2 and the other by turning the element under test off. The theory of the proposed calibration method is given, and the closed form formulation of the element amplitude and phase distortions is derived. From the mathematical point of view, it is the minimum required measurements that use two scalar values to determine one complex vector. Numerical simulations and experiments are conducted to validate and demonstrate the effectiveness of the proposed calibration method.